Boehmeria nivea (L.) Gaud. ameliorate oxidative stress-mediated inflammatory Responses and apoptosis in LPS/CSC-induced chronic obstructive pulmonary disease mouse model - Lee, Ba-Wool; Ha, Ji-Hye; Yi, Da-Hye; Kim, Ju-Hong; Jeong, Seong-Hun; Jeong, Ju Hwan; Jung, Kyungsook; Jeong, Hyung Jae; Park, Ji-Young; Kim, Woo Sik; Ryu, Young-Bae; Kwon, Hyung-Jun; et al. (Frontiers in Pharmacology, 2026)
IntroductionBoehmeria nivea (L.) Gaud. has traditionally been regarded as a medicinal food with applications in various inflammatory disorders. However, its role in chronic obstructive pulmonary disease (COPD) has not yet been clarified.MethodsIn this study, the preventive efficacy of the ethyl acetate fraction of B. nivea (L.) Gaud. leaves (EA-BN) was evaluated in a COPD model established by intratracheal instillation of lipopolysaccharide (LPS; 0.5 mg/kg body weight) and cigarette smoke condensate (CSC; 12.5 mg/kg body weight) in male C57BL/6N mice. The experimental groups received dexamethasone (3 mg/kg) as a positive control or EA-BN at doses of 100 and 200 mg/kg.ResultsEA-BN administration significantly reduced T helper 1 cytokine levels and decreased macrophage and neutrophil counts in bronchoalveolar lavage fluid. Histological analyses revealed that EA-BN mitigated alveolar destruction and inflammatory infiltration, whereas pulmonary function tests demonstrated improvements in the FEV0.1/FVC ratio and lung elastance in the LPS/CSC-induced COPD. Additionally, EA-BN alleviated oxidative stress by promoting the nuclear translocation of Nrf2 and enhancing the expression of its downstream targets, HO-1 and NQO1, leading to a reduction in reactive oxygen species and nitric oxide production. EA-BN downregulated thioredoxin-interacting protein and NLRP3 inflammasome activation, thereby suppressing caspase-1 and IL-1β expression, whereas also attenuating apoptosis by modulating the Bax/Bcl-2/caspase-3 pathway.DiscussionCollectively, these findings suggest that EA-BN possesses antioxidant, anti-inflammatory, and anti-apoptotic properties, supporting its potential as a preventive agent against COPD.